On the etymology of Lithuanian dangus - Petit, Daniel (Baltistica, 2021)
Traditionally the Baltic name of the ‘sky’ (Lith. dangùs, Old Pr. dangus) is explained as derived from the verb deñgti ‘to cover’, based on the assumption that the sky was conceived of as a kind of curved surface covering the world. However, this traditional approach has left two questions open until now: (1) how to explain the formation of the word dangus, which is more akin to that of an adjective than to that of a noun; (2) how to reconstruct the PIE prehistory of this Baltic lexical family. The aim of this paper is to discuss both the morphological and the semantic structure of the word dangus and to explain all its features, by proposing a new hypothesis on its origin and development.
Keywords: Lithuanian; etymology; historical linguistics